What do adolescents with asthma really think about adherence to inhalers? Insights from a qualitative analysis of a UK online forum - De,Simoni A; Horne,R; Fleming,L; Bush,A; Griffiths,C (BMJ OPEN, 2017)
Objective To explore the barriers and facilitators to inhaled asthma treatment in adolescents with asthma.Design Qualitative analysis of posts about inhaler treatment in adolescents from an online forum for people with asthma. Analysis informed by the Perceptions and Practicalities Approach.Participants Fifty-four forum participants (39 adolescents ≥16 years, 5 parents of adolescents, 10 adults with asthma) identified using search terms ‘teenager inhaler’ and ‘adolescent inhaler’.Setting Posts from adolescents, parents and adults with asthma taking part in the Asthma UK online forum between 2006 and 2016, UK.Results Practical barriers reducing the ability to adhere included forgetfulness and poor routines, inadequate inhaler technique, organisational difficulties (such as repeat prescriptions), and families not understanding or accepting their child had asthma. Prompting and monitoring inhaler treatment by parents were described as helpful, with adolescents benefiting from self-monitoring, for example, by using charts logging adherence. Perceptions reducing the motivation to adhere included asthma representation as episodic rather than chronic condition with intermittent need of inhaler treatment. Adolescents and adults with asthma (but not parents) described concerns related to attributed side effects (eg, weight gain) and social stigma, resulting in ‘embarrassment of taking inhalers’. Facilitators to adherence included actively seeking general practitioners’/consultants’ adjustments if problems arose and learning to deal with the side effects and stigma. Parents were instrumental in creating a sense of responsibility for adherence.Conclusions This online forum reveals a rich and novel insight into adherence to asthma inhalers by adolescents. Interventions that prompt and monitor preventer inhaler use would be welcomed and hold potential. In clinical consultations, exploring parents’ beliefs about asth